Impact of functional endoscopic sinus surgery on otologic symptoms associated with chronic rhinosinusitis - Deora, Kapil Nath; Patel, Arun Kumar; Verma, Rakesh Kumar; Kumari, Asha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: The study was aimed at observing the impact of FESS on otologic symptoms associated with Chronic rhinosinusitis. Otitis media and other otologic symptoms develop frequently during the evolution of CRS. The evolution of middle ear disease in the setting of chronic rhino-snusitis possibly reflects the role of a dynamic conduit, eustachian tube, normal functioning of which, is crucial to keep the middle ear functions within physiologic limits. Methods: The study was conducted in the Department of Otorhinolaryngology, Jhalawar Medical College and SRG hospital, Jhalawar (Rajasthan) between August 2021 and November 2022. 53 patients of CRS with associated otologic symptoms were included in the study. Patients were subjected to functional endoscopic sinus surgery and septoplasty where relevant. Results: The majority of the study patients presented with ear discharge (72%), earache (41%) and ear fullness (41%). The most common sinusitis related symptoms were Nasal blockage (77%), frontal headache (53%) and nasal discharge (49%) with relatively lower proportion of post nasal drip (23%), facial pain (21%) and halitosis (15%). All participants were subjected to FESS which was combined with septoplasty and sub-mucous diathermy of the inferior turbinate where it was relevant. Patients were followed at 1st, 3rd and 6th week post-operatively. Conclusions: Majority of the patients (89%) shown a statistically significant subjective improvement in the otologic symptoms following the initial optimum medical therapy for the CRS. Endoscopic sinus surgery was found to improve symptoms on a statistically significant scale.